2001
DOI: 10.1023/a:1009472416305
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Endometrial receptivity is tolerant to a wide duration of E2 treatment (until 2 months), while waiting for oocytes available for donation, but best results are achieved with a treatment range of 11 to about 40 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(13 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…In our study, the longest duration of estrogen administration was 26 days, and no breakthrough bleeding was observed in the study population. On the other hand, unopposed estrogen administration within a range of 11-40 days has been shown to result in the best pregnancy outcomes, and shorter durations have been correlated with high rates of early pregnancy loss [10,11], which is consistent with our results. The rates of biochemical and clinical pregnancies were signi cantly higher in the late initiation group than in the early initiation group, whereas the ongoing pregnancy rate was similar between the two groups.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the longest duration of estrogen administration was 26 days, and no breakthrough bleeding was observed in the study population. On the other hand, unopposed estrogen administration within a range of 11-40 days has been shown to result in the best pregnancy outcomes, and shorter durations have been correlated with high rates of early pregnancy loss [10,11], which is consistent with our results. The rates of biochemical and clinical pregnancies were signi cantly higher in the late initiation group than in the early initiation group, whereas the ongoing pregnancy rate was similar between the two groups.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, there does not appear to be an upper limit for the duration of estrogen stimulation. However, one study has reported that prolonged unopposed estrogen administration beyond 40 days is associated with a high rate of breakthrough bleeding [10]. In our study, the longest duration of estrogen administration was 26 days, and no breakthrough bleeding was observed in the study population.…”
Section: Discussionmentioning
confidence: 39%
“…This slight tendency to better results with longer oestrogen exposure contrasts with previous studies found in the literature, which have claimed that shorter periods of oestrogen exposure are more beneficial to pregnancy outcome [less than 24 days until progesterone onset in Bourdon et al (4) and less than 20 days in Sunkara et al (6)]. In addition, Borini and Younis proposed the optimal length of oestrogen exposure in oocyte donation cycles to be between 12 and 19 days (7,8). In contrast, we didn't see any significant drop in pregnancy rates beyond 19 days (Table 3), also in line with previously evidences proving that periods of oestrogen exposure longer than 35 days in oocyte donation cycles do not hamper clinical outcomes (14).…”
Section: Discussionmentioning
confidence: 69%